2004
DOI: 10.3346/jkms.2004.19.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Bystander-Mediated Regression of Murine Neuroblastoma via Retroviral Transfer of the HSV-TK Gene

Abstract: Selective introduction of genes conferring chemosensitivity into proliferating tumor cells may be used to treat cancer. We investigated the bystander effect of retrovirusmediated gene transfer of herpes simplex virus thymidine kinase (HSV-TK) gene to murine neuroblastoma cell line (neuro-2a) in vitro and in vivo, and we examined whether the mechanism of bystander effect in neuroblastoma would also depend on connexin-dependent gap junction and/or immune response. A strong bystander effect was observed in vitro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…38 Because of the bystander effect, it has been reported that HSVTK gene transduction of 10-20% of tumor cells in vivo can eliminate the whole tumor. 38,39 Our results showed that the efficiency of the NT-polyplex transfection in vivo is in the range of 8-12% as determined by RFP gene expression. However, the transfection of the HSVTK gene only caused the reduction of tumor weight and size by 50%.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…38 Because of the bystander effect, it has been reported that HSVTK gene transduction of 10-20% of tumor cells in vivo can eliminate the whole tumor. 38,39 Our results showed that the efficiency of the NT-polyplex transfection in vivo is in the range of 8-12% as determined by RFP gene expression. However, the transfection of the HSVTK gene only caused the reduction of tumor weight and size by 50%.…”
Section: Discussionmentioning
confidence: 75%
“…21,22 This effect includes the transfer of toxic metabolic products of GCV through gap junctions, which are dependent on connexin expression. 38 Other mechanisms related to HSVTK-GCV-mediated bystander effect are fagocytosis of the apoptotic vesicles 39 and the immune response against the tumor. 38 Because of the bystander effect, it has been reported that HSVTK gene transduction of 10-20% of tumor cells in vivo can eliminate the whole tumor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that HSV-TK/GCV therapy induces anti-tumor immunity 63 , 64 and even regression of brain tumors in immunocompetent rats and neuroblastoma in a murine model 65 , 66 . In the treated tumors, a marked infiltration of inflammatory cells, predominantly CD4+ and CD8+, is observed.…”
Section: Suicide Gene Therapymentioning
confidence: 99%
“…Se ha evidenciado que la terapia con HSV-TK/GCV induce inmunidad anti-tumoral 63 , 64 e incluso, regresión de tumores cerebrales en ratas inmunocompetentes y de neuroblastoma en un modelo murino 65 , 66 . En los tumores tratados se observa una marcada infiltración de células inflamatorias, con predominio de CD4+ y CD8+, lo que sugiere que el sistema HSV-TK/GCV estimula la respuesta inmune antitumoral 50 , 60 .…”
Section: Terapia Génica Suicidaunclassified